Exploring entrepreneurial intentions: integrating Kolb’s experiential learning theory with Ajzen’s theory of planned behaviour - Pushparaj M. Nayak; Madhukara Nayak; Harisha G. Joshi (Cogent Social Sciences)
This study investigated the influence of experiential learning (EL) on entrepreneurial intention (EI) of the students through the lens of perceived behavioural control (PBC). To present a comprehensive perspective, we have explored the direct influence of the antecedents associated with the theory of planned behavior (TPB). The data for were collected via a structured questionnaire from 1,250 final-year management science students. The study employed the partial least squares structural equation modelling method approach for data analysis. The results confirm positive relationships between EL and EI (β = 0.266). In addition, PBC mediates and enhances the relationship between EL and EI (β = 0.30). The result also showed that the TPB antecedents, namely entrepreneurial attitude, subjective norms, and PBC, significantly and positively influence students’ EIs. The proposed model explains a 64% variance in EIs. Moreover, the influence of EL on EI gets stronger when PBC acts as a mediator. Therefore, it is necessary to concentrate on PBC and EL.The study has valuable insights and practical and theoretical implications forhigher education institutions, and policymakers on making more informed resource allocations and fostering an environment conducive to entrepreneurship.